Outcomes with loncastuximab tesirine following CAR T-cell therapy in patients with relapsed or refractory diffuse large B-cell lymphoma - Narendranath Epperla; Melanie Lucero; Tom Bailey; Laura Mirams; Jolenta Cheung; Mona Amet; Gary Milligan; Lei Chen (Blood Cancer Journal)
Abstract The efficacy of loncastuximab tesirine (lonca) following chimeric antigen receptor T-cell therapy (CAR-T) progression/failure is unknown. Hence, we sought to examine real-world use and outcomes of lonca following CAR-T in patients with relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL) in the USA. In this retrospective study, we included adults (age ≥ 18 years) with R/R DLBCL who received lonca monotherapy as third- (3 L) or fourth line (4 L) treatment after progressing on second line (2 L) or 3 L CAR-T, respectively. Post-CAR-T lonca outcomes included response rates (overall response rate [ORR] and complete response [CR] rate), duration of response (DOR), progression-free survival (PFS), and overall survival (OS). A total of 118 patients were included in the analysis with 95 receiving lonca following 2 L CAR-T (median age:66 years; 61% male) and 23 following 3 L CAR-T (median age:57 years; 43% male). Patients with 2 L CAR-T/3 L lonca had an ORR of 73% (CR rate of 34%). With a median follow-up of 8.5 months following lonca initiation, median DOR, PFS, and OS were not reached. The DOR, PFS, and OS at 12 months were 68%, 77%, and 84%, respectively. Patients with 3 L CAR-T/4 L lonca had an ORR of 78% (CR rate of 17%). With a median follow-up of 13 months following lonca initiation, the median DOR and PFS were 7.6 and 12.0 months, while median OS was not reached. OS at 12 months was 95%. In this study, we found that lonca monotherapy was an effective treatment option in R/R DLBCL in 3 L and 4 L settings including those who were resistant to or progressed after CAR-T.